Comparison of del Nido cardioplegia and St. Thomas Hospital solution – two types of cardioplegia in adult cardiac surgery - Mishra, Prashant; Jadhav, Ranjit B.; Mohapatra, Chandan Kumar Ray; Khandekar, Jayant; Raut, Chaitanya; Ammannaya, Ganesh Kumar; Seth, Harsh S.; Singh, Jaskaran; Shah, Vaibhav (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Introduction: St. Thomas’ cardioplegic solution No. 2 (ST), although most widely used in adult cardiac surgery, needs to be given at short intervals, causing additional myocardial injury. Aim: To determine whether del Nido (DN) cardioplegia, with longer periods of arrest, provides equivalent myocardial protection as compared to ST. Material and methods: The study population comprised 100 patients who underwent elective coronary artery bypass grafting (CABG) or double valve replacement (DVR) surgery between January 2015 and January 2016. The patients were divided into two groups based on the type of cardioplegia administered during surgery: 1) intermittent ST (ST, n = 50) and 2) DN cardioplegia (DN, n = 50). We compared the aortic cross clamp (CC) and cardiopulmonary bypass (CPB) times, number of intra-operative DC shocks required, and postoperative changes in left ventricular ejection fraction (LVEF) in the two groups. Results : The aortic cross clamp and bypass times were shorter with DN (110.15 ±36.84 vs. 133.56 ±35.66 and 158.60 ±39.92 vs. 179.81 ±42.36 min respectively, p < 0.05). Fewer cardioplegia doses were required in the DN group vs. the ST group (1.38 ±0.59 vs. 4.15 ±1.26; p = 0.001), while a single cardioplegia dose was given to 35 DN patients (70%) vs. 0 ST patients (p < 0.001). Postoperative LVEF was better preserved in the DN group. Conclusions : The use of DN leads to shorter cross clamp and CPB times, reduces cardioplegia dosage, and provides potentially better myocardial protection in terms of LVEF preservation, with a safety profile comparable to ST cardioplegia.